Calibration of the Performance of Bidirectional Shaker Table in Centrifuge Model Tests Using Sensor Networks - Hongjun Li; Hong Zhong; Xuedong Zhang; Yanyi Zhang; Yujing Hou (International Journal of Distributed Sensor Networks)
Great concern for the safety of high rock-fill dams which are being or to be built in the southwestern area of China with high seismicity is attracted. In order to obtain an in-depth knowledge of the mechanism of seismic-induced damage and reasonable assessment of the seismic design for rock-fill dams, comprehensive dynamic centrifuge tests which can simulate and reproduce strictly the action process of strong earthquake should be conducted. Thus, the performance and accuracy of test device have become a key problem. In the present research, refined calibration of bidirectional shaker table, which can be actuated in both horizontal and vertical directions simultaneously and placed on the swing bucket, was achieved via the distributed sensor network used in a centrifuge model test. The seismic input at the dam site and transmission along the dam axis were obtained by the five pairs of accelerometers. The extensive usage of the sensor networks technology in physical model test in centrifuge has significantly promoted the calibration of performance of bidirectional shaker table and would thus enable further insight into the dynamic response of rock-fill dam.